EMERGENCY MEDICAL DISPATCH: DO THE DEAD TAKE PRIORITY OVER THE DYING?. Issue 5 (18th April 2015) - Hitt, Andy; Williams, Julia; Edwards, Tim
Abstract : Background: In the UK demand for emergency ambulances is increasing. To deal with this increase, Ambulance Service Trusts must use resources effectively and ensure that they are deployed appropriately. Aim: The aim of this study was to gain an understanding of factors influencing resource dispatchers' (RD) decision-making processes when managing ambulance resources attending out-of-hospital cardiac arrest (OOHCA) and how these decisions might impact on resource availability. Method: Utilising a generic qualitative approach, nine RDs participated in semi structured interviews which were recorded and transcribed verbatim. Data analysis was performed using a template style of thematic analysis. Findings: OOHCA generally takes priority over other emergency calls regardless of clinical need or likely prognosis. Participants stated that they would probably drive past a critically ill patient to attend a patient in cardiac arrest even if they believed them to be beyond help. A significant amount of time was spent dealing with deceased patients, especially when waiting for police to attend. This may affect resource availability and subsequently delay treatment of other critically ill and injured patients. Limitations: Dispatching processes may differ between Trusts so further studies are required to enhance transferability of findings. Conclusions: OOHCA is almost always prioritised above other time critical emergencies despite the view that other patients may benefit more from a priority response. Decisions are made rapidly, under pressure and with very little clinical information to hand. Recommendations for change: Further research is required before substantive recommendations can be made but preliminary indications infer that resource efficiency may be improved by applying simple changes to every day practice including dialogue between lead clinician and dispatcher to optimise staff skill mix in attendance to calls and improved liaison between police and ambulance controls to facilitate the prompt stand down of ambulance resources dealing with deceased patients.